Building a Psychological Capital Cultivation Ecosystem for Financial Industry Graduates based on the PERMA Model: A Case Study of the "Credit Management + Psychological Capital" Dual-Core Driven Model - Zhong, Feng; Guo, Jiana; Li, Yingmei (International Journal of Social Sciences and Public Administration, 2025)
Facing the industry characteristics of "high pressure, high competition, and high ethical requirements," finance graduates commonly exhibit an "adaptability deficit" in Psychological Capital (PsyCap) during their "campus-to-workplace" transition. Traditional "problem-oriented" psychological intervention models are insufficient to meet the needs of the new era's financial talent for "potential-stimulation" and "positive development." This paper introduces the PERMA model from Positive Psychology, aiming to construct a qualitative, developmental ecosystem for cultivating psychological capital. Using theoretical modeling and case analysis methods, this study eschews quantitative analysis to deeply explore the internal synergistic mechanisms of "Credit Management" professional education and "Psychological Capital" cultivation (the "Dual-Core Drive"). The core contributions of this paper are: First, it theoretically deconstructs the cultivation paths from the PERMA model (Positive Emotion, Engagement, Relationships, Meaning, Accomplishment) to psychological capital (Hope, Resilience, Efficacy, Optimism). Second, it "contextualizes" and reorganizes the PERMA model into a "four-in-one" cultivation ecosystem: the "Value-Guided Ethical Seminar" system (corresp. to M: Meaning), the "Professional Empowerment & Skill Training" system (corresp. to E/A: Engagement/Accomplishment), the "Positive Support & Peer-Assisted" system (corresp. to R: Relationships), and the "Resource Spillover & Cloud Replenishment" system (corresp. to P: Positive Emotion). The study argues that this ecosystem, through the "dual-core driven" model, internalizes professional ethics into psychological capital, transcending the traditional paradigm of separating "psychology" from "profession." It provides a replicable theoretical model and practical path for cultivating financial talents who are unified in "core stability" and "technical excellence."